Analisis Strategi Pemasaran Dalam Meningkatkan Volume Penjualan (Studi pada Salafiyah Bakery Maospati Magetan) - Suparno, Rizqi Firdaus; Istiqaroh, Choirum Rindah; Mutmainah, Mutmainah (Jurnal Mahasiswa Manajemen, 2023)
Background - Identification of internal company factors and external environmental factors that affect the company. Objectives - This study aims to identify the right and competitive strategy for Salafiyah Bakery. Design/ Methodology/ Approach - Conducted using the SWOT analysis method. (Strengths, Weaknesses, Opportunities, Threats). This research method is a qualitative approach using a descriptive analysis method on 4 respondents, namely business owners and 2 bakery employees and 1 consumer. Data collection was carried out by observation, interviews, questionnaires submitted by respondents, and documentation. Then the data obtained from the results of data collection were analyzed using SWOT, IFAS, EFAS and IE analysis. Based on the results of the internal factor analysis, 6 strengths and 6 weaknesses were found. While the external factors identified were 6 opportunities and 5 threats. Conclusion - Based on the analysis of the results of the IFAS matrix, it produced a value of 2.74 and the EFAS matrix produced a figure of 3.22. In the IE matrix diagram, this study shows that the Salafiyah Bakery business is in the growth quadrant which is in the second quarter, which means that the company can implement a growth strategy. Research Limitations - This study has several limitations. First, the research time is relatively short. Second, one of the key informants in this study was difficult to contact, which resulted in a lack of important information from relevant perspectives. These limitations can affect the quality of the data collected and the analysis conducted.